The prevalence of high risk obstructive sleep apnoea among patients with type 2 diabetes in Jordan. (June 2019) - Saad, Ahmad M.J.; Hiyasat, Dana; Jaddou, Hashem; Obeidat, Nathir
Abstract: Objective: To estimate the prevalence of Obstructive Sleep Apnea (OSA) among patients with type 2 Diabetes Mellitus (T2DM) in Jordan, and to explore the association between sleep apnea and clinical and demographic variables. Method: A cross-sectional study was carried out from the 1st of November 2011 to the 1st of February 2012 on 1143 patients with T2DM (aged 30–90 years) at the National Center for Diabetes, Endocrinology, and Genetics (NCDEG). The center is considered to be the only referral center in the country and accordingly, the patients represent the population in different parts of the country. All participants completed the Arabic version of the Berlin Questionnaire and were categorized as either low or high-risk patients for OSA. Results: A total of 1143 patients with T2DM were included in this study. There were 587 (51.4%) males and 556 (48.6%) females. The findings showed that 554 (48.5%) patients were at high risk for OSA and 589 (51.5%) were low risk for OSA. Logistic regression analysis revealed that age, smoking, and neck circumference were significantly correlated with high risk for OSA. The clinical and demographic variables were also collected for analysis. Conclusions: The study found that high risk for OSA was highly prevalent among Jordanian patients with T2DM and that age, smoking and neck circumference were significantly correlated with OSA. Health care providers should be made aware of the high prevalence of sleep problems affecting patients with diabetes and should consider the appropriate screening and treatment for these patients, therefore improving their quality of life.